Improving the economic analysis of control interventions for diseases of trade: Lessons from two case studies of FMD control in South East Asia - Randolph, Thomas F.; Perry, Brian D.; Horst, H.S.; Agbayani, A.; Benigno, C.; Kalpravidh, W.; Gleeson, L.J. (International Society for Veterinary Epidemiology and Economics, 2000)
With the continuing globalization of trade and the evolving regulatory environment under the World Trade Organization, there has been renewed interest in many developing countries to review disease control policies that may affect their trade in livestock and livestock products. In particular, a number of countries are reassessing the possibility of eradicating Foot and Mouth Disease (FMD). Cost-benefit analysis is often used in such circumstances to compare among a set of specified policy options. This paper identifies a number of key methodological shortcomings of such analyses, drawing upon two recent case studies of FMD control in South East Asia, offers recommendations for improving their comprehensiveness and quality.